Molecular mechanism of the synergistic effects of vitrification solutions on the stability of phospholipid bilayers - Hughes, Z.; Mancera, Ricardo (Cell Press, 2014)
The vitrification solutions used in the cryopreservation of biological samples aim to minimize the deleterious formation of ice by dehydrating cells and promoting the formation of the glassy state of water. They contain a mixture of different cryoprotective agents (CPAs) in water, typically polyhydroxylated alcohols and/or dimethyl sulfoxide (DMSO), which can damage cell membranes. Molecular dynamics simulations have been used to investigate the behavior of pure DPPC, pure DOPC, and mixed DOPC-ß-sitosterol bilayers solvated in a vitrification solution containing glycerol, ethylene glycol, and DMSO at concentrations that approximate the widely used plant vitrification solution 2. As in the case of solutions containing a single CPA, the vitrification solution causes the bilayer to thin and become disordered, and pores form in the case of some bilayers. Importantly, the degree of thinning is, however, substantially reduced compared to solutions of DMSO containing the same total CPA concentration. The reduction in the damage done to the bilayers is a result of the ability of the polyhydroxylated species (especially glycerol) to form hydrogen bonds to the lipid and sterol molecules of the bilayer. A decrease in the amount of DMSO in the vitrification solution with a corresponding increase in the amount of glycerol or ethylene glycol diminishes further its damaging effect due to increased hydrogen bonding of the polyol species to the bilayer headgroups. These findings rationalize, to our knowledge for the first time, the synergistic effects of combining different CPAs, and form the basis for the optimization of vitrification solutions.